Patients and informal caregivers' experience of surgical and transcatheter aortic valve replacement: Real‐world data contributing to establish value‐based medicine in Denmark. Issue 4 (14th March 2019) - Rosseel, Liesbeth; Bieliauskas, Gintautas; Brodersen, Bente B.; Olsen, Peter S.; Søndergaard, Lars; De Backer, Ole
Abstract : Background: The concept of value‐based medicine (VBM) is increasingly implemented in therapeutic decision‐making processes, but only few data on patient‐perceived values are available in the field of aortic stenosis treatment. Hypothesis: This study aimed to deliver data on patient‐perceived values and health‐related quality of life (HR‐QoL) following surgical aortic valve replacement (SAVR) and transcatheter aortic valve replacement (TAVR) in a real‐world, all‐comers patient population. Methods: Questionnaires were sent to 637 patients who had undergone elective AVR 12 to 24 months earlier in the period September 2015 to August 2016. The questionnaires were specifically designed to assess physical and mental impact of the entire AVR process on patients and their nearest relative and to capture HR‐QoL. Results: Questionnaires were completed by 429 patients (SAVR: N = 265; TAVR: N = 164). Both physical and mental impact of the intervention and its recovery period were experienced more stressful by SAVR as compared with TAVR patients. Also, nearest relatives of SAVR patients experienced the entire process mentally more stressful and enduring than relatives of TAVR patients. In both groups, 10% of patients reported no change in HR‐QoL, whereas HR‐QoL improved in 76% vs 83% ( P = 0.092) and worsened in 14% vs 7% ( P = 0.040) of the SAVR and TAVR populations, respectively. Conclusion: The perioperative experience tends to be more stressful for SAVR as compared with TAVR patients; however, HR‐QoL finally improves to a similar degree in both groups. Given the increasing importance of VBM, patient‐perceived values will have to be considered in future decision‐making processes, both at individual and public policy‐making level.